Robotic-Assisted Laparoscopic Surgery for Rectal Cancer (RALS): A Review of the Literature - Emil Filipov; Tsvetomir Ivanov (Journal of Biomedical & Clinical Research)
Surgical treatment of rectal cancer is still difficult even in big centers. The limited pelvic space, problematic operative exposure, complex surgeries with more common anastomotic complications make the results unsatisfying. After the concept of total mesorectal excision (TME) was introduced by Heald, the results have improved dramatically. Advances in technology added further excitement about awaited promising results. Surgeons tried to apply all new methods to search for the best treatment: – atraumatic, painless, safe, with low recurrence rates, fast recovery, with an acceptable price, and easy to learn or teach. Robotic-assisted laparoscopic surgery (RALS) was introduced to overcome the limitations of conventional laparoscopic and open surgery and improve on their main advantages.A non-systematic literature review on the articles on RALS in the PubMed and Scopus database was performed. RALS, robotic-assisted laparoscopic surgery, and rectal cancer keywords were used. The search was restricted to articles in English, with main endpoints of interest on short-term and long-term surgical results and oncological outcomes. Fifty-seven articles from Europe, the USA, and Asia were identified. RALS was tried in large series in patients with different pathology and showed its values. However, there are still many controversies on its superiority, cost, and advantages. RALS is safe and efficient in experienced hands. It could be superior to conventional laparoscopic surgery (CLS). Its advantages in oncological outcomes over CLS are to be proven in structured randomized clinical trials (RCTs).